Kinetic and Methodological Insights into Hydrophilic Drug Release from Mesoporous Silica Nanocarriers - Rodrigo Rozas; Andrea C. Ortiz; Sofía Peñaloza; Sebastián Lizama; Mario E. Flores; Javier Morales; Francisco Arriagada (Pharmaceutics, 2025)
Background/Objectives: The absence of standardized protocols for assessing in vitro drug release from nanocarriers poses significant challenges in nanoformulation development. This study evaluated three in vitro methods: sample and separate without medium replacement (independent batch), sample and separate with medium replacement, and a dialysis bag method, to characterize the release of rhodamine B from mesoporous silica nanoparticles (MSNs). Methods: Each method was examined under varying agitation conditions (shaking versus stirring). MSNs were synthesized via the sol-gel method, exhibiting a hydrodynamic diameter of 202 nm, a zeta potential of −23.5 mV, and a surface area of 688 m2/g, with a drug loading efficiency of 32.4%. Results: Release profiles revealed that the independent batch method exhibited a rapid initial burst followed by a plateau after 4 h, attributed to surface saturation effects. Conversely, the sample and separate with medium replacement method sustained the release up to 60% over 48 h, maintaining sink conditions. The dialysis method showed agitation-dependent variability, with magnetic stirring using a longer stir bar enhancing release. Kinetic analyses indicated first-order kinetics with non-Fickian diffusion. Conclusions: Overall, the results indicate that both the selection of the in vitro method and the agitation technique play a crucial role in determining the apparent drug release kinetics from nanocarriers. These findings highlight the critical role of experimental design in interpreting nanocarrier release kinetics, advocating for tailored protocols to improve reproducibility and in vitro–in vivo correlations in nanoformulation.